레이저 후열처리 공정을 통한 저온공정형 IGZO 박막 트랜지스터의 특성 개선에 관한 연구 - 이재윤; Jae-yun Lee; Anvar Tukhtaev; 유수창; Suchang Yoo; 김용환; Yong-hwan Kim; 최성곤; Seong-gon Choi; 유흥균; Heung Gyoon Ryu; 정용진; et al. (대한금속·재료학회지, 60(8), 2022)
High-performance thin-film transistors (TFTs) produced at low temperatures are required for ultrahigh- resolution and flexible display applications. The scientific community has been studying unconventional techniques to investigate low voltage flexible devices and low power flexible circuits for the past decade. In particular, metal oxide semiconductors, such as indium gallium zinc oxide (IGZO), have made significant progress as amorphous silicon replacements for electronics and commercial displays. On the other hand, developing metal oxide transistors with low processing temperatures remains a difficulty. The hightemperature annealing process causes very instability in the plastic substrate. Here, we introduce IGZO TFTs that shows enhanced electrical properties environmental stability by laser post-annealing. After annealing process, the laser post-annealing process was given at 80 MHz, pulse width 140 fs, for 50 seconds. The improved electrical characteristics of this laser post-annealed IGZO TFTs were: 9.03 cm 2 /Vs; 2.2×10 7 on/off current ratio. The IGZO TFT to which laser post-annealing was applied had a flat surface, and it was confirmed that the combination of internal metal and oxygen was urged, and the leakage current problem was improved by suppressing excessive generation of oxygen vacancy. Furthermore, the voltage transfer curve was measured after fabricating the N-MOS logic inverter circuit, this inverter showed a value of 80.8% the total noise margin. (Received 23 March, 2022; Accepted 23 May, 2022)